Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I have this integral: $$\int_{-20}^{20}\sqrt{2+t^2}\,dt$$

I tried solving it many times but without success.

The end result is this: $$2\left( 10\sqrt{402}+\mathop{\mathrm{arcsinh}}(10\sqrt{2})\right).$$

I can't seem to get this end result. I got a few wrong ones but cant find this one. Perhaps it's wrong? Could anyone confirm it?

I tried Sage, and it calculates it correctly, but not with steps.

share|improve this question
    
You do not "solve" integrals, but rather "evaluate" them. –  Argon May 21 '12 at 16:49
    
Did you try the substitution $t= \sqrt{2} \sinh(x)$? –  Fabian May 21 '12 at 16:55
    
Have a look the example too .math.stackexchange.com/questions/120981/… –  Mathlover May 21 '12 at 18:01

4 Answers 4

up vote 2 down vote accepted

Another way integrate $\sqrt{2 + t^2}$ is to use the Euler substitution $u = \sqrt{2+t^2} + t$. Subtracting $t$ and squaring gives $t = \frac{1}{2}(u - \frac{2}{u})$. This implies

$$\sqrt{2+t^2} = u - t = \frac{1}{2}(u + \frac{2}{u})$$

and

$$dt = \frac{1}{2}(1 + \frac{2}{u^2})\,du$$

Thus \begin{align*} \int \sqrt{2+t^2}\,dt &= \int \frac{1}{4}(u + \frac{4}{u} + \frac{4}{u^3})\,du \\ &= \frac{1}{8}u^2 - \frac{1}{2u^2} + \ln{|u|} + C \\ &= \frac{1}{8}(u - \frac{2}{u})(u + \frac{2}{u}) + \ln{|u|} + C \\ &= \frac{1}{2}t\sqrt{2 + t^2} + \ln(t + \sqrt{2 + t^2}) + C \end{align*}

Applying this antiderivative to your integral, you get $$20\sqrt{402} + \ln(20 + \sqrt{402}) - \ln(-20 + \sqrt{402}) = 2(10\sqrt{402} + \ln(10\sqrt{2} + \sqrt{201}))$$

You can check that $\ln(10\sqrt{2} + \sqrt{201}) = \operatorname{arcsinh}(10\sqrt{2})$ so that this solution is the same as the one in your question.

share|improve this answer

While I was writting this answer, Artem posted his. My answer is essentially his 1st one.

Let $f(t)=\sqrt{2+t^{2}}$. Since $f(-t)=$ $f(t)$, we have

$$\begin{equation*} I=\int_{-20}^{20}\sqrt{2+t^{2}}dt=2\int_{0}^{20}\sqrt{2+t^{2}}dt \end{equation*}$$

As the integrand $f(t)$ is a quadratic irrational we can also use the following Euler substitution $$\begin{eqnarray*} x &=&\sqrt{2+t^{2}}-t\Leftrightarrow t=\frac{2-x^{2}}{2x}\Leftrightarrow \sqrt{2+t^{2}}=\frac{2+x^{2}}{2x} \\ dt &=&-\frac{2+x^{2}}{2x^{2}}dx, \end{eqnarray*}$$ which transforms the integrand into a rational fraction in $x$ $$\begin{eqnarray*} \int \sqrt{2+t^{2}}dt &=&\int \frac{2+x^{2}}{2x}\left( -\frac{2+x^{2}}{2x^{2} }\right) dx \\ &=&-\int \frac{1}{x}+\frac{1}{x^{3}}+\frac{x}{4}dx \\ &=&-\left( \ln \left\vert x\right\vert -\frac{1}{2x^{2}}+\frac{x^{2}}{8} \right) +C. \end{eqnarray*}$$ The limits of integration of $I/2$ are $$\begin{eqnarray*} t &=&0,x=\sqrt{2} \\ t &=&20,x=\sqrt{2+20^{2}}-20=\sqrt{402}-20. \end{eqnarray*}$$ Thus $$\begin{eqnarray*} I &=&\left. -2\left( \ln \left\vert x\right\vert -\frac{1}{2x^{2}}+\frac{ x^{2}}{8}\right) \right\vert _{\sqrt{2}}^{\sqrt{402}-20} \\ &=&2\ln \left( \frac{\sqrt{2}}{\sqrt{402}-20}\right) +\frac{1}{\left( \sqrt{ 402}-20\right) ^{2}}-\frac{\left( \sqrt{402}-20\right) ^{2}}{4}+\frac{1}{2}. \end{eqnarray*}$$

share|improve this answer

The typical way to start dealing with an integral that has $\sqrt{a^2+t^2}$ (in your case, $a=\sqrt{2}$) is to use a trigonometric substitution or a hyperbolic substitution.

If we use hyperbolic substitution, we want to use the fact that $$1 + \sinh^2 z = \cosh^2 z.$$ Set $t=\sqrt{2}\sinh z$. Then $$\sqrt{2 + t^2} = \sqrt{2 + 2\sinh^2z} = \sqrt{2(1+\sinh^2 z)} = \sqrt{2\cosh^2 z} = \sqrt{2}\cosh z.$$ Also, if $t=\sqrt{2}\sinh z$, then $dt =\sqrt{2}\cosh z\,dz$. Therefore, $$\int\sqrt{2+t^2}\,dt = \int \sqrt{2}\cosh z \sqrt{2}\cosh z\,dz = 2\int\cosh^2 z\,dz.$$ Now we need to solve the integral of $\cosh^2 z$. We can do this by parts, similarly to how we solve the integral of $\cos^2t$. Let $u=\cosh z$, $dv=\cosh z\,dz$. Then $du=\sinh z\,dz$, $v=\sinh z$, so $$\begin{align*} \int\cosh^2 z\,dz &= \cosh z\sinh z - \int \sinh^2z\,dz\\ &= \cosh z \sinh z - \int(cosh^2z - 1)\,dz\\ &= \cosh z\sinh z +z - \int\cosh^2z\,dz. \end{align*}$$ Hence $$\begin{align*} \int\cosh^2z\,dz &= z + \cosh z\sinh z - \int\cosh^2z\,dz\\ 2\int\cosh^2z\,dz &= z+ \cosh z\sinh z + C\\ \int\cosh^2 z\,dz &= \frac{1}{2}z + \frac{1}{2}\cosh z\sinh z + C. \end{align*}$$ Then to get it back into a function of $t$ we remember that $t=\sqrt{2}\sinh z$, so $\sinh z = \frac{\sqrt{2}}{2}t$. Then $z= \mathop{\mathrm{arcsinh}}\left(\frac{\sqrt{2}}{2}t\right)$, and $$\sinh z\cosh z = \sinh z \sqrt{1+\sinh^2z} = \frac{\sqrt{2}}{2}t\sqrt{1 + \frac{1}{2}t^2} = \frac{1}{2}\sqrt{2+t^2}.$$ Therefore, $$\int\sqrt{2+t^2}\,dt = 2\int\cosh^2z\,dz = 2\mathop{\mathrm{arcsinh}}\left(\frac{\sqrt{2}}{2}t\right) + \sqrt{2+t^2}+C.$$ Now plugging into the definite integral gives you a solution.


If we use trigonometric substitutions, we want to use the fact that $$1 + \tan^2 \theta = \sec^2\theta$$ Set $t=\sqrt{2}\tan\theta$, with $-\frac{\pi}{2} \lt \theta\lt\frac{\pi}{2}$. Then $$\sqrt{2+t^2} = \sqrt{2+2\tan^2\theta} = \sqrt{2}\sqrt{1+\tan^2\theta} = \sqrt{2}\sqrt{\sec^2\theta} = \sqrt{2}|\sec\theta|.$$ Since $\sec\theta\gt 0$ on $-\frac{\pi}{2}\lt \theta\lt \frac{\pi}{2}$, we get that $\sqrt{2+t^2} = \sqrt{2}\sec\theta$.

Also, if $t=\sqrt{2}\tan\theta$, then $dt = \sqrt{2}\sec^2\theta\,d\theta$. Therefore, $$\int\sqrt{2+t^2}\,dt = \int \sqrt{2}\sec\theta\sqrt{2}\sec^2\theta\,d\theta = 2\int\sec^3\theta\,d\theta.$$

So we need to find $\int\sec^3\theta\,d\theta = \int\frac{1}{\cos^3\theta}\,d\theta$.

This can be done any number of ways. Using integration by parts, we get $$\int\frac{d\theta}{\cos^3\theta} = \frac{1}{2}\tan\theta + \frac{1}{2}\int\frac{d\theta}{\cos\theta}.$$ And $$\int\frac{d\theta}{\cos\theta} = \int\sec\theta\,d\theta = \ln|\sec\theta + \tan\theta|+C.$$ Thus, we get that $$\int\sqrt{2+t^2}\,dt = \tan\theta + \ln|\sec\theta+\tan\theta|+C.$$ To change it into a formula using $t$, we use the fact that $t=\sqrt{2}\tan\theta$. Therefore, $\tan\theta = \frac{\sqrt{2}}{2}t$; and $$\sec\theta = \sqrt{1 + \tan^2\theta} = \sqrt{1 + \frac{t^2}{2}} = \frac{\sqrt{2}}{2}\sqrt{2+t^2}.$$ Plugging in and evaluating gives the desired result.

share|improve this answer

Here are two more ways to calculate $\int \sqrt{a^2+x^2}\ dx$.

  1. Let us make the substitution $\sqrt{a^2+x^2}=t-x$. After squaring, $a^2=t^2-2xt$, from which $$ x=\frac{t^2-a^2}{2t}\,. $$ Using the last expression, one finds $$ \sqrt{a^2+x^2}=t-x=\frac{t^2+a^2}{2t}\,, $$ and $$ dx=\frac{t^2+a^2}{2t^2}dt. $$ Plugging everything into the integral, $$ \frac 14\int\left(\frac{2a^2}{t}+t+\frac{a^4}{t^3}\right)dt=\frac{a^2}{2}\ln t+\frac{t^4-a^4}{8t^2}+C. $$ Note, that from the above $x\sqrt{a^2+x^2}=\frac{t^4-a^4}{4t^2}$, therefore we obtain finally $$ \int\sqrt{a^2+x^2}\,dx=\frac{a^2}{2}\ln(x+\sqrt{a^2+x^2})+\frac{1}{2}x\sqrt{a^2+x^2}+C. $$
  2. Consider the integration by parts: $$ u=\sqrt{a^2+x^2},\quad v=x,\quad du=\frac{x}{\sqrt{x^2+a^2}}. $$ Therefore, $$ \int\sqrt{x^2+a^2}\,dx=x\sqrt{a^2+x^2}-\int\frac{x^2dx}{\sqrt{a^2+x^2}}=\\ x\sqrt{a^2+x^2}-\int\frac{x^2+a^2-a^2 dx}{\sqrt{a^2+x^2}}=\\x\sqrt{a^2+x^2}-\int\sqrt{a^2+x^2}\,dx+\int\frac{a^2dx}{\sqrt{a^2+x^2}}. $$ It is known (and can easily be found with the variable change from my point 1) that $$ \int\frac{dx}{\sqrt{a^2+x^2}}=\ln(x+\sqrt{a^2+x^2})+C, $$ hence, finally, $$ \int\sqrt{a^2+x^2}\,dx=\frac{a^2}{2}\ln(x+\sqrt{a^2+x^2})+\frac{1}{2}x\sqrt{a^2+x^2}+C. $$
share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.